All Days 1993
DOI: 10.2118/26622-ms
|View full text |Cite
|
Sign up to set email alerts
|

WAG Process Optimization in the Rangely CO2 Miscible Flood

Abstract: A miscible C02 project was initiated in the Rangely Weber Sand Unit in northwest Colorado in 1986, Over the past seven years, the project has expanded areally to include 80% of the Unit, and substantial investments have been completed in injection, production and gas recompression facilities. As the project matures, emphasis has shifted from adding new C02 injection patterns to management of C02 injection, with goals of maximizing recovery and reducing operating costs. Optimization of the Water-Alternating-Gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…The improved gas handling and oil recovery have been reported for SWAG injection at Siri field (Berg et al 2002 andQuale et al 2000), the Joffre Viking (Stephenson et al 1993) CO 2 miscible flood and SWAG emulation at the Rangely CO 2 miscible flood (Attanucci et al 1993). Pilot tests performed on Kuparuk River Field in Alaska Stoisits et al 1995) have also demonstrated the feasibility of SWAG injection.…”
mentioning
confidence: 86%
“…The improved gas handling and oil recovery have been reported for SWAG injection at Siri field (Berg et al 2002 andQuale et al 2000), the Joffre Viking (Stephenson et al 1993) CO 2 miscible flood and SWAG emulation at the Rangely CO 2 miscible flood (Attanucci et al 1993). Pilot tests performed on Kuparuk River Field in Alaska Stoisits et al 1995) have also demonstrated the feasibility of SWAG injection.…”
mentioning
confidence: 86%
“…The feasibility of CO 2 injection for either light or heavy oil recovery has been shown by various laboratory investigations. Several field trials have also shown a considerable increase in oil production after CO 2 injection. In light oil systems, miscibility between CO 2 and the oil is usually a target, and it is often achievable by increasing reservoir pressure or enriching the injection fluid . However, in the case of medium or heavy oil reservoirs, the decrease in the interfacial tension (IFT) is not as significant as that in the light oil systems, and the contact between the oil and CO 2 would remain immiscible .…”
Section: Introductionmentioning
confidence: 99%
“…Water blocking may become a severe effect in water-wet reservoirs during carbon dioxide (CO 2 ) flooding. As a consequence of water blocking, during the processes of conventional CO 2 injection, continuous/slug CO 2 injection, simultaneous water and gas injection (SWAG), and water alternating gas injection (WAG), , a considerable amount of the residual oil is hindered from being contacted by the injected CO 2 . Such a continuous water phase, which is the water-blocking effect, greatly reduces the microscopic displacement efficiency. To eliminate the water-blocking effect in CO 2 injection, active carbonated water is applied as a preflush prior to a CO 2 flood …”
Section: Introductionmentioning
confidence: 99%